THE TEXT OF CAXTON'S SECOND EDITION OF THE CANTERBURY TALES - Bárbara, Bordalejo (International Journal of English Studies, 2009)
This article describes recent research on the textual relationship between the first and second editions of the Canterbury Tales printed in England by William Caxton and it also explores the textual affiliations of the manuscript source for the corrections in the second edition. Using both computerised and manual methods the variant readings between the first and second editions of the Tales are isolated. Examples of the textual affiliations of the manuscript source of Caxton's second edition are analysed. This article concludes that the manuscript source for the corrections introduced in Caxton's second edition of the Tales was of the same quality as tlie best extant manuscripts and that its readings can help our understanding of the textual tradition and can clarify the text for editors of the Tales.